Foam fractionation for effectively recovering copper from the discarded printed circuit board of personal computer. Issue 5 (24th March 2021) - Qin, Shaojie; Sun, Pengkun; Wu, Zhaoliang; Liu, Wei; Yang, Chunyan
ABSTRACT: In this work, copper (Cu) was recovered from the discarded printed circuit board (PCB) of personal computer through foam fractionation. The discarded PCB was treated by acid leaching. The leaching yield of Cu ion reached 97.61% under the conditions of temperature 40ºC, nitric acid concentration 6 mol/L and leaching time 60 min. A novel foam fractionation column was developed to strengthen foam drainage. Under the suitable conditions of pH 4.0, volumetric airflow rate 70 mL/min, SDS concentration 0.12 g/L and loading liquid volume 500 mL, enrichment ratio and recovery percentage of Cu ion were 29.1% and 90.2%, respectively.